C-reactive protein and white blood cell count in cardiogenic shock - Dudda, Jonas; Schupp, Tobias; Rusnak, Jonas; Weidner, Kathrin; Abumayyaleh, Mohammad S. A.; Ruka, Marinela; Egner-Walter, Sascha; Forner, Jan; Müller, Julian; Bertsch, Thomas; Kittel, Maximilian; Akın, Ibrahim; et al. (Journal of Clinical Medicine, 2023)
This study examines the prognostic impact of C-reactive protein (CRP) and white blood cell (WBC) counts in patients with cardiogenic shock (CS). Data regarding the prognostic impact of inflammatory biomarkers in CS are scarce. All consecutive patients with CS from 2019 to 2021 admitted to a cardiac intensive care unit (ICU) were included at one institution. Laboratory measurements were retrieved from the day of admission (i.e., day 1), as well as days 2, 3, 4, and 8. The primary endpoint was 30-day all-cause mortality. Statistical analyses included univariate t-tests, Spearman’s correlations, C-statistics, Kaplan-Meier, and Cox regression analyses. From a total of 240 consecutive patients admitted with CS, 55% died within 30 days. CRP levels on days 3 to 8 were associated with reliable discrimination for 30-day all-cause mortality (area under the curve (AUC): 0.623-0.754), whereas CRP on day 1 was not (AUC = 0.514). In line, CRP > 100 mg/L on day 3 (56% vs. 37%; log-rank p = 0.023; HR = 1.702; 95% CI 1.060-2.735; p = 0.028) and especially a CRP increase of at least 200% from days 1 to day 3 (51% vs. 35%; log-rank p = 0.040; HR = 1.720; 95% CI 1.006-2.943; p = 0.048) were associated with an increased risk of all-cause mortality. Furthermore, WBC on day 1 discriminated 30-day all-cause mortality (AUC = 0.605; p = 0.005) with an increased risk of all-cause mortality in patients admitted with WBC > 10 × 106/mL (59% vs. 40%; log-rank p = 0.036; HR = 1.643; 95% CI 1.010-2.671; p = 0.045). In conclusion, WBC count on admission as well as CRP levels during the course of ICU treatment were associated with 30-day all-cause mortality. Specifically, an increase of CRP levels by at least 200% from day 1 to day 3 during the course of ICU treatment was associated with an increased risk of 30-day all-cause mortality. The present study is one of the first to describe the prognostic value of inflammatory biomarkers in consecutive all-comer CS patients treated at a cardiac ICU.
Gesehen am 15.07.2024